Phospholipid‐flipping activity of P4‐ATPase drives membrane curvature. (29th March 2018) - Takada, Naoto; Naito, Tomoki; Inoue, Takanari; Nakayama, Kazuhisa; Takatsu, Hiroyuki; Shin, Hye‐Won
Abstract: P4‐ATPases are phospholipid flippases that translocate phospholipids from the exoplasmic/luminal to the cytoplasmic leaflet of biological membranes. All P4‐ATPases in yeast and some in other organisms are required for membrane trafficking; therefore, changes in the transbilayer lipid composition induced by flippases are thought to be crucial for membrane deformation. However, it is poorly understood whether the phospholipid‐flipping activity of P4‐ATPases can promote membrane deformation. In this study, we assessed membrane deformation induced by flippase activity via monitoring the extent of membrane tubulation using a system that allows inducible recruitment of Bin/amphiphysin/Rvs (BAR) domains to the plasma membrane (PM). Enhanced phosphatidylcholine‐flippase activity at the PM due to expression of ATP10A, a member of the P4‐ATPase family, promoted membrane tubulation upon recruitment of BAR domains to the PM. This is the important evidence that changes in the transbilayer lipid composition induced by P4‐ATPases can deform biological membranes. Synopsis: Phosphatidylcholine‐flipping at the plasma membrane can induce inward membrane curvature and membrane tubule formation upon recruitment of BAR domains to the plasma membrane. Recruitment of BAR domains to the plasma membrane can generate membrane tubules in cells expressing P4‐ATPase, ATP10A, but not its ATPase‐deficient mutant. Hypotonic stress, which increases membrane tension and prevents inward bending of the plasma membrane, abrogates the formation of membrane tubules. Increased inward plasma membrane bending by ATP10A expression facilitates endocytosis. Abstract : Phosphatidylcholine‐flipping at the plasma membrane can induce inward membrane curvature and membrane tubule formation upon recruitment of BAR domains to the plasma membrane.